A Model of Cultivation of the Buddhist Way of Life in a Cultural Approach to Foreign Tourists - Wilkie, Chatreudee; Ruksat, Suvin (The Journal of International Buddhist Studies College, 2025)
This study aims to: (1) explore theoretical concepts related to cultural tourism, (2) study the cultivation of the Buddhist way of life, (3) develop a culture-based model for such cultivation, and (4) present new knowledge with practical applications. Addressing a significant research gap, the study proposes and validates a systematic framework for transmitting Buddhist values to foreign tourists through cultural engagement. A qualitative, phenomenological approach was employed, involving 45 key informants, comprising training organisers, foreign tourists, and subject experts. Data were collected through documentary analysis, participant observation, in-depth interviews, and focus group discussions, with all procedures conducted in accordance with ethical standards for human research. Thematic content analysis, inductive reasoning, and trustworthiness verification were used to ensure rigour, and findings are presented descriptively alongside a proposed model. The results indicate that cultural tourism fosters deeper engagement with local values and traditions. In Thailand, Buddhist culture motivates tourists to explore and internalise the beliefs, practices, and aesthetic elements of Buddhist spaces. Monasteries provide structured and supportive environments for learning, particularly through the Four Foundations of Mindfulness, while monks act as facilitators who transmit essential teachings in English. The proposed culture-based model consists of four dimensions: (1) residing in peaceful environments, (2) cultivating ethical conduct through loving-kindness and role models, (3) engaging in ritual practices with meaningful explanations, and (4) reflecting on Buddhist principles such as karma, samsara, impermanence, and Nirvana. From these findings emerges the SMVIT model, Serenity, Masterpiece, Voice, and Immersion through meditation and reflection, which collectively lead to the Transformation of Worldview. This framework contributes both to cultural tourism and Buddhist education, offering temples and retreat centres practical strategies for engaging foreign tourists and fostering sustainable spiritual transformation as a form of Buddhist soft power.